Java practical guide for programmers - Sikora, Zbigniew M. (Amsterdam ; Boston : Morgan Kaufmann, 2003)
If you're an experienced programmer, you already have a rock-solid foundation for learning Java. All you need is a resource that takes your experience into account and explains Java's key principles and techniques in an intelligent, efficient way. Java: Practical Guide for Programmers is precisely that resource. Here, you won't have to wade through hundreds of pages of overly simplistic material to learn the basics of Java programming. Instead, you get highly focused instruction in the core elements of Java 1.4, accompanied by carefully chosen examples and line-by-line analyses that are right to the point. You'll be astonished at how soon you can begin productive coding in Java, and how quickly your skills will progress. Web resources: Source code from the book is no longer available at http://www.zm.sikora.btinternet.co.uk/source.html Please press the 'Companion Page' button on the upper right side of this page to access a zip file containing it. Sun J2SE download page http://java.sun.com/j2se/downloads.html Sun J2SE API documentation http://java.sun.com/j2se/1.4.1/docs/index.html * Written expressly for people who already know a procedural or object-oriented programming language. * Takes a concise approach designed to make the most of the experience you already have. * Covers the core elements of Java 1.4, including language syntax, OO features, collections, exception handling, input/output, threads, event handling, and Swing components. * Filled with incisive coding examples and line-by-line analyses. * Via a companion Web site, provides downloadable example code and links to additional resources.
Basic language syntax -- Flow control -- Classes and objects -- Inheritance and access control -- Exceptions -- Input/output -- Developing GUIs -- Collections -- Threads.
Keywords: Java (Computer program language).; Electronic books